Rowley Jefferson's awesome friendly adventure - Kinney, Jeff (Puffin Books, Penguin Random House Children's, 2021)
Adventure awaits! From the imagination of Rowley Jefferson comes an adventure of epic proportions. Join Roland and his best friend, Garg the Barbarian, as they leave the safety of their village and embark on a quest to save Roland's mom from the White Warlock. Will our heroes survive? Find out in Rowley Jefferson's Awesome Friendly Adventure!